(untitled) (Scientific journal of the Fergana State University, 2023)
The paper considers a method for calculating the dynamic characteristics of spherical shells partially filled with a liquid, taking into account arbitrary boundary conditions, wall thickness variability, and an arbitrary filling level. At the same time, a method for a simplified solution of the problem of vibrations of a spherical shell partially filled with liquid is presented. From the analysis of the obtained numerical results, it follows that the form of vibrations of a spherical shell filled with liquid is of an oscillatory nature. The amplitude of the shell vibrations increases with a change in the level of its filling.